Kajian Ketidaksesuaian Dimensi Elemen Struktur Pada Gedung Di Kabupaten Subang - Eko Walujodjati; Hilman Januar Ramadhan (Jurnal Konstruksi, 2026)
This research examines the dimensional non-conformity of structural elements in the Subang Regency Transportation Agency Building. The purpose of this research is to identify and analyze the factors causing dimensional non-conformity of structural elements that can affect the integrity and safety of the building. The methodology used is the analysis of planning documents and construction implementation. The results showed that there were several structural elements that experienced dimensional discrepancies, which were caused by various factors such as planning errors, inaccuracies in implementation, and the use of materials that did not meet specifications. The implications of these findings indicate the need for increased supervision and quality control during the planning and execution stages of construction to ensure the dimensional conformity of structural elements in accordance with established standards. This research is expected to contribute to efforts to improve the quality of building construction in Subang Regency as well as in other regencies or cities.